Your own RISC. (Economist, 2019)
The article reports on popularity of RISC-V, an open-source hardware instruction set architecture (ISA) that was originally written by computer scientists at the University of California, Berkeley, who wanted an instruction set that they could use for publishable research. Topics discussed include advantages of RISC-V over chips based on proprietary designs, and reasons for the proliferation of RISC-V.